2010
DOI: 10.1103/physrevlett.104.207801
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Orientation Coupling in Equilibrium Polymer Melts

Abstract: The motion in concentrated polymer systems is described by either the Rouse or the reptation model, which both assume that the relaxation of each polymer chain is independent of the surrounding chains. This, however, is in contradiction with several experiments. In this Letter, we propose a universal description of orientation coupling in polymer melts in terms of the time-dependent coupling parameter κ(t). We use molecular dynamics simulations to show that the coupling parameter increases with time, reaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 11 publications
1
59
0
Order By: Relevance
“…In the previous papers 4,6,11,12) , the origin of the cross-correlation was suggested to be the force balance and the osmotic force. These two forc- On the other hand, the cross-correlation between different chains is observed for the present model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the previous papers 4,6,11,12) , the origin of the cross-correlation was suggested to be the force balance and the osmotic force. These two forc- On the other hand, the cross-correlation between different chains is observed for the present model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular simulations by Cao and Likhtman 4) mentioned above have revealed that the cross-correlation does exist even in melts of bead-spring chains for which nematic interaction is rather weak. Recent studies by the multi-chain slip-link simulations 6,11,12) suggest that the cross-correlation is due to the force balance around entanglement and/or the osmotic force that suppresses density fluctuations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations